Melampaui Kegigihan: Dukungan Sosial Sebagai Jalur Dari Grit Menuju Flourishing Pada Mahasiswa Tingkat Akhir - Nia Kusuma Wardhani; Ros Patriani Dewi (CV. AFDIFAL MAJU BERKAH, 2026)
Final-year university students experience significant academic and psychological demands that may compromise their well-being, making flourishing a critical indicator of optimal functioning. While grit has been widely recognized as a predictor of resilience and well-being, its underlying mechanisms remain underexplored, particularly in relation to social support. This study examines the mediating role of social support in the relationship between grit and flourishing among final-year students. A quantitative cross-sectional survey was conducted with 239 participants selected through purposive sampling. Data were collected using the PERMA-Profiler, the Short Grit Scale (Grit-S), and the Multidimensional Scale of Perceived Social Support (MSPSS), and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that grit significantly predicts both social support and flourishing, while social support also has a significant positive effect on flourishing. Importantly, social support fully mediates the relationship between grit and flourishing, indicating that the effect of grit on well-being operates primarily through relational mechanisms. These findings advance a relational perspective on grit and highlight the importance of integrating personal strengths with supportive social environments in promoting student well-being